Respuesta :

Answer:

5. (x,y) = (2.3)

Step-by-step explanation:

1/2x + 2 = x+1

x = 2

y = 2+1

y = 3

(x,y) + (2,3)

{3 = 1/2 x 2 + 2

{3 = 2 + 1

{3 = 3

{3 = 3

Answer:

  3. no solution

  5. (x, y) = (2, 3)

Step-by-step explanation:

3.

  -5x +y = 1

  -10x +2y = -2

Multiply the first equation by -2 and add the second equation:

  -2(-5x +y) +(-10x +2y) = -2(1) +(-2)

  10x -2y -10x +2y = -2 -2 . . . . eliminate parentheses

  0 = -4 . . . . . . . . . no variable values will make this true: NO SOLUTION

(The lines graph as parallel lines.)

__

5.

  y = 1/2x +2

  y = x +1

Subtract the first equation from the second:

  (y) -(y) = (x +1) -(1/2x +2)

  0 = 1/2x -1

  0 = x -2

  2 = x

  y = x +1 = 2 +1 = 3 . . . . use the second equation to find y

The solution is (x, y) = (2, 3).